Análise cinemática dos membros inferiores e morfofuncional dos músculos do quadril e suas relações com a cinética de mulheres com e sem dor patelofemoral - Nunes, Guilherme Silva (2018)
Approximately 10% to 20% of the population is affected by patellofemoral pain (PFP), with higher prevalence in females. Last years, proximal factors to the knee joint have been related to PFP, such as poor control of hip movements in weight-bearing activities and weakness in hip muscles. The objectives of the present thesis were to compare females with and without PFP regarding muscle function of the hip and knee muscles, morphology of the gluteus medius and maximus, landing biomechanics from jumps, and to correlate muscle function and kinematic outcomes with the impact measure during landings. The objective of the present thesis were also to compare individuals with and without PFP regarding hip muscle function clinically evaluated and to review the literature regarding the methods for patellofemoral stress calculation. Hip abductors and extensors and knee extensors muscle function (rate of force development, power and torque) was evaluated using an isokinetic dynamometer. Morphology of the gluteal musculature was evaluated using ultrasonography. Landing biomechanics was assessed using a camera system and force plate. For the clinical evaluation, hip abductors and extensors strength was evaluated isometrically using hand-held dynamometer and dynamically using 10 repetitions maximum tests, hip abduction and extension power were assessed using a linear position transducer, and endurance was assessed using the maximum number of repetitions. Females with PFP had deficits in muscle function compared to asymptomatic females including lower power and strength of hip abductors and extensors and knee extensors. During landings, females with PFP generated greater impact combined to lower hip, knee and ankle range of motion in the sagittal plane. Clinically evaluated, individuals with PFP had lower strength and power of hip abductors and extensors compared to asymptomatic individuals. Finally, the literature presents inconsistencies regarding the methods for patellofemoral stress calculation and no valid method is defined as gold standard. Therefore, different factors related to muscle function should be considered during PFP rehabilitation, especially muscle power. Interventions targeting impact and movement control during landings may also be useful.